Implementation of AHP in Establishing a Priority Scale for the Use of Operational Funds in BLUD Hospitals - Rosida, Alya; Rahman, Andri Nur; Marliadi, Reny; Hasymi, Liana Fitriani; Hastuti, Eny (Dinasti Publisher, 2025)
There is a need to increase the effectiveness and efficiency with which the operational fund budget is managed at RSUD Brigjend H. Hasan Basry Kandangan. Declining revenue projections and limited resources mean that hospitals must determine budget priorities in an objective and measurable way. This research aims to analyse the application of the Analytical Hierarchy Process (AHP) method to determine operational fund budget priorities, providing recommendations to support more effective decision-making in a hospital environment. A qualitative approach was used, involving data collection through interviews and documentation, and analysis using the AHP method with the assistance of Expert Choice 11 software to compare criteria and service alternatives. The results showed that the main criteria for determining budget priorities are potential income, market demand, operational costs and limited resources. The analysis prioritised home care services due to their high revenue potential and market demand. The application of AHP has also been proven to increase the efficiency, transparency and accountability of budget decision-making processes. This study concludes that the AHP method can be an effective tool for BLUD Hospital's operational budget prioritisation process. It is recommended that the method be integrated into all work units and supported by training for optimal application.